2012
DOI: 10.1177/2047487312460516
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-based cardiac rehabilitation improves endothelial function assessed by flow-mediated dilation but not by pulse amplitude tonometry*

Abstract: We aimed to investigate the effect of exercise on endothelium-dependent vasodilator function assessed simultaneously in the brachial artery and in the distal arterial bed by flow-mediated dilation and the pulse amplitude tonometry method, respectively, in coronary artery disease patients. The study included 146 patients with stable coronary artery disease (123 men, mean age 62 ± 9 years) who participated in the Cardiac Rehabilitation and Genetics of Exercise performance study. All patients completed a 12-week … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 29 publications
(33 reference statements)
2
29
0
Order By: Relevance
“…Previous studies have shown that FMD improves after exercise-based cardiac rehabilitation in CAD patients [27][28][29]. In accordance to our results, Currie et al [30] found similar improvements after AIT and MCT, while Wisløff et al [14] and Tjonna et al [31] found larger increases after AIT compared to MCT.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have shown that FMD improves after exercise-based cardiac rehabilitation in CAD patients [27][28][29]. In accordance to our results, Currie et al [30] found similar improvements after AIT and MCT, while Wisløff et al [14] and Tjonna et al [31] found larger increases after AIT compared to MCT.…”
Section: Discussionsupporting
confidence: 93%
“…Afterwards, the FMD had significantly increased and the endothelial function had improved for the CR group, as previously reported. This study is meaningful as it shows that FMD test with less than six weeks of aerobic exercise can enhance endothelial function, while previous studies verified endothelial function improvement with longer than twelve [18] or eight weeks of aerobic exercise [19]. …”
Section: Discussionmentioning
confidence: 66%
“…Cornelissen et al [18] reported that FMD test was done for patients with coronary artery disease, who had undergone a 12-week aerobic exercise to find that the aerobic exercise group showed a significant FMD increase and endothelial function improvement before and after exercise, compared to the control group. In this study, patients with coronary artery disease underwent six-week aerobic exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Cornelissen et al demonstrated a significant increase in FMD% following 12 weeks of aerobic exercise in stable CAD patients [12]. Similarly, Luk et al conducted research to determine the effect of 8 weeks of AEXT on FMD in patients with stable CAD and demonstrated significant improvements in FMD [13].…”
Section: Discussionmentioning
confidence: 99%